Highly Stretchable and Conductive Silver Nanoparticle Embedded Graphene Flake Electrode Prepared by In situ Dual Reduction Reaction - Yoon, Yeoheung (Sci Rep, 2015)
The emergence of stretchable devices that combine with conductive properties offers new exciting opportunities for wearable applications. Here, a novel, convenient and inexpensive solution process was demonstrated to prepare in situ silver (Ag) or platinum (Pt) nanoparticles (NPs)-embedded rGO hybrid materials using formic acid duality in the presence of AgNO(3) or H(2)PtCl(6) at low temperature. The reduction duality of the formic acid can convert graphene oxide (GO) to rGO and simultaneously deposit the positively charged metal ion to metal NP on rGO while the formic acid itself is converted to a CO(2) evolving gas that is eco-friendly. The AgNP-embedded rGO hybrid electrode on an elastomeric substrate exhibited superior stretchable properties including a maximum conductivity of 3012 S cm(-1) (at 0 % strain) and 322.8 S cm(-1) (at 35 % strain). Its fabrication process using a printing method is scalable. Surprisingly, the electrode can survive even in continuous stretching cycles.